Effect of Family Training on Profitability of Small-Scale Broiler Farming in Joypurhat District (The Agriculturists, 2015)
This study was conducted to compare the productivity and profitability of trained and non-trained small-scale broiler farmers in the Joypurhat district of Bangladesh. A total number of sixty farmers were trained on the modern techniques for profitable and sustainable broiler farming. The study showed that the mortality of broiler was 2.90±0.89 percent and 11.30±2.29 percent for trained and non-trained farmers, respectively (P